Gambaran School Well-Being pada Peserta Didik Program Kelas Akselerasi di SMA Negeri 8 Yogyakarta - Khatimah, Husnul (Universitas Ahmad Dahlan, 2015)
This research is about the school well-being of acceleration students in SMA Negeri 8 Yogyakarta. A Researcher wants to describe the school well-being and its main factors which contribute to acceleration studentsâ school well-being in SMA Negeri 8 Yogyakarta.Â The data is collected by interview, observation, and document study. The research shows that the school well-being of acceleration students inÂ SMA Negeri 8 Yogyakarta are described as well perceived on school infrastructure, excellent individual capital, unwell learning design management, well interpersonal school interaction, well school management, and perceived parental support.